Security and Privacy in Mobile Information and Communication Systems Second International ICST Conference, MobiSec 2010, Catania, Sicily, Italy, May 27-28, 2010, Revised Selected Papers - Schmidt, Andreas U.; Russello, Giovanni.; Lioy, Antonio.; Prasad, Neeli R.; Lian, Shiguo. (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2010)
MobiSec 2010 was the second ICST conference on security and privacy in mobile information and communication systems. With the vast area of mobile technology research and application, the intention behind the creation of MobiSec was to make a small, but unique contribution to build a bridge between top-level research and large scale application of novel kinds of information security for mobile devices and communication.